The Use of Geofencing in Android-Based Mobile Applications for Promotional Ads in Shopping Centers - Yodi Susanto; Persis Haryo Winasis; Muhammad Maulana Rachman; Heriyanto Heriyanto (UNIVERSITAS RAHARJA, 2023)
This paper describes the implementation of geofencing technology in Android-based mobile applications for promotional advertisements based on the user's location. Geofencing is a location-based service that uses GPS, cellular networks, or Wi-Fi to create virtual geographic boundaries around specific locations. This technology enables businesses to send targeted advertisements to mobile users based on their current location. The paper presents the development of an Android-based mobile application that uses geofencing technology to provide location-based promotional advertisements to users. Researchers use one of the big shopping centers in Jakarta as a location object for geofencing technology. The application uses Google Maps and Firebase to create geofences around specific locations, and then sends push notifications to users within the geofenced areas. The implementation also includes a backend system to manage the promotional advertisements and user data. The results show that the implementation of geofencing technology in Android-based mobile applications can provide a more targeted and effective way to deliver promotional advertisements to users.